ASSESSMENT OF THE EFFECT OF BIG DATA ANALYTICS ON ACCOUNTING INFORMATION QUALITY IN NIGERIA (Journal of Global Accounting, 2025)
In the past years, accounting information quality has posed a big challenge to firms, stakeholders, industry watchers and the accounting profession globally. It is against this backdrop that the big data analytics emerged as one of the solutions to this dilemma. This study therefore critically assessed the effect of big data analytics on accounting information quality in an under researched sector, the hospitality sector in Lagos. Evidence obtained from the responses of 102 accountants and 50 IT staff selected through purposive sampling technique served as the source of data. These raw data were subjected to detailed descriptive tests and regression analyses. Findings here proved that velocity of data and variety of data had positive and significantly strong effect on the quality of accounting information while volume of data had a smaller positive significance. It is therefore imperative to recommend amongst others that firms should integrate the adoption of big data analytics into mainstream accounting activities and accountants should also prioritize their technological development in order to meet up with the rapidly increasing demands of stakeholders.
Keywords: Accounting Information Quality; Big Data Analytics; Financial Reports